Exploring Chinese herbal medicine for the treatment of inflammatory bowel disease: A comprehensive overview - Jeetendra Kumar Gupta; Aniruddh Pratap Singh; Yati Sharma (Elsevier, 2024)
Introduction: Inflammatory Bowel Disease (IBD) is a recurrent and chronic inflammatory disorder that impacts the gastrointestinal tract. It is distinguished by a multiple etiology, including various complicated factors. The global prevalence of IBD has increased in recent years, leading to a need for novel strategies in its management. This has sparked interest in exploring alternative medicines, such as herbal medicine, for the treatment of IBD. In this context, Chinese Herbal Medicine (CHM), which has a strong foundation in traditional practices, has garnered attention as a potentially successful exploration route owing to its diverse medicinal characteristics. Methodology: Different keywords, including IBD, CHM and Gut microbiota, were employed in searches across online databases like Scopus, Web of Science, Google Scholar, and PubMed. Duplicate references, inappropriate articles, and incomplete data were debarred which lies outside the scope of this artcle. Results: Although conventional treatments have demonstrated efficacy in certain patients, they frequently entail undesirable side effects and inherent constraints. This study provides a comprehensive analysis of the existing research literature about the effectiveness of several Chinese herbal formulations in reducing the symptoms associated with IBD and influencing the composition of the gut microbiota. Significant importance is attributed to comprehending the deep interrelationship between host-microbiota interactions and the intricate microbial populations that inhabit the gastrointestinal system. Discussion: The discussion delves into a comprehensive exploration of Chinese Herbal Medicine as a potential treatment option for Inflammatory Bowel Disease. This comprehensive review examines the diverse facets of complementary and alternative medicine in the management of IBD, encompassing its historical background, fundamental principles, the scientific rationale behind its effectiveness, and its practical implementation in clinical settings.